LANGUAGE STYLE USED BY MAIN CHARACTER “MIGUEL” IN “COCO” DISNEY’S MOVIE - Triana, Sakila Ade; Nur, Riola Haya; Weda, Sukardi (Journal of English Literature and Linguistic Studies, 2023)
Various types of language styles can be observed in small things in life and in different utterances. Each different environment will have a different language style. The researcher looked into the style of language in the film script entitled COCO. In this study, the researcher intends to learn the main character's choice of language, who is "Miguel". There are two studies in this research. First, the researchers classify all kinds of figurative language used by the main character "Miguel" in "COCO: Disney's Movie”. Second, it explains all the factors that influence the characters in using different language styles. This study uses sociolinguistics as an approach to discuss the use of figurative language and to find out the social factors that influence the use of stylistic language by characters in film scripts. The data is a COCO movie script. Data was collected by watching films, reading film scripts, and classifying language styles. The researcher chose the dialogue spoken by the main character. After collecting the data, the researcher differentiates and classifies these utterances into several types of figurative language using the theory of Martin Joos (1976). Then, the researcher found factors that might influence the character to use language style by using social factor theory by Holmes and Wilson (2017). The findings show that there are four types of figurative language used by Miguel, the main character in the COCO film. The kinds of language are formal style, casual style, consultative style, and intimate style. The most dominant style of language used by the main character is the casual style (41%). The main character tends to use a relaxed style of language to create a more comfortable and relaxed atmosphere. There are four social factors that influence the two main characters to use figurative language, the four social factors are participant, setting, topic, and function.